Pola Akumulasi Prolin dan Poliamin Beberapa Aksesi Tanaman Terung pada Cekaman Kekeringan - Kurniawati, Siti; Khumaida, Nurul; Ardie, Sintho Wahyuning; Hartati, N. Sri i; Sudarmonowati, Enny (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACT Drought stress is one of the major limiting factors for plant growth and production. Therefore, the mechanism of drought tolerance is important to be studied. Eggplant (Solanum spp.) is relatively tolerant to drought stress compared to other member of Solanaceae family. The objective of this study was to study the mechanism of drought tolerance in eggplant related to accumulation pattern of proline and polyamines. Seven eggplant accessions were drought stressed for 21 days and rewatered for the following next 7 days. Drought stress treatment significantly decreased the soil water content and reduced plant height of all accessions. Eggplant responded the drought stress by reducing stomatal density and stomatal opening to reduce transpiration rate. Drought stress also induced proline and polyamine (PA) accumulation in the leaf tissues. These accumulations started at 14-days after drought stress period when soil water content less than 20% and reached their peaks at 21 days after drought stress. The highest level of proline (134.70 μmol g-1) and that of putrescine (20.836 ng g-1) could be used as indicators for eggplant drought stress condition. Keywords: physiological responses, polyamine (PA), proline, putrescine, stomata